Diagnostic Analysis of Misconceptions in Alkenes and Alkynes Using a Three-Tier Test - Asyti Febliza; Herdini Herdini (Department of Chemistr Education Faculty of Teacher Training and Education Universitas Su, 2026)
This study aims to analyze students' misconceptions on the topics of alkenes and alkynes in organic chemistry learning using a three-tier diagnostic test based on the certainty of response index (CRI). The research subjects consisted of 39 chemistry education students. The test instruments included three levels: multiple-choice answers, essay-type reasons, and a confidence level of 0–5. The data were classified into categories of understanding the concept, misconception, and not knowing the concept. The results revealed that 55% of the respondents understood the concept, 30% had misconceptions, and 15% did not know the concept. The highest misconceptions appeared in the subconcepts of alkene and alkyne addition reactions, Markovnikov's rule, reaction product prediction, and rearrangement. In-depth analysis revealed three main patterns of misconceptions, namely, false positive understanding, robust misconception, and strong misconception, with the latter type being most dominant in terms of mechanistic concepts. Misconceptions arose because of the rote application of rules, inappropriate generalization, and failure to read molecular structural information. These findings emphasize the need for learning strategies based on dual representation and cognitive conflict to reduce misconceptions and improve conceptual understanding in organic chemistry.